The mediating role of board size, philanthropy and working capital management between basic corporate governance factors and firm's performance - Shahid, Muhammad Naeem (University of Economics Ho Chi Minh City, 2023)
Purpose This study aims to identify the impact of corporate governance on performance of sugar mills. In order to study this relation, a model is constructed in which ownership structure and independent directors are taken as independent variables. Whereas firm performance is analyzed by using proxy variables such as return on asset (ROA), return on equity (ROE) and sales growth. Moreover, size of board, working capital management (WCM) and philanthropy are taken as mediating variables between governance variables and firm performance. Design/methodology/approach The data of 32 sugar mills listed at Pakistan Stock Exchange for the period of four years (i.e. 2014–2017) is used for this research. Moreover, to investigate the model, generalized least squares statistical method is used to measure the relationship between variables. Findings The results revealed that there is significant but positive relationship between independent directors and ROA while ownership structure and ROE have significant but negative relationship. Thus, the board of directors should make it sure that all stakeholders and organizations should increase the nonfamily ownership in firms for better corporate performance. Moreover, philanthropy and WCM mediate the relationship between corporate governance and firms' performance. Practical/implications This research work will be helpful in the corporate governance, and further researchers can conduct their study by considering executive/nonexecutive director and institutional owners as governance variables. Originality/value This paper fulfills an identified need to study how Corporate Governance effect the performance of firm.